Tissue-specific metabolomic profiling after cardiopulmonary bypass in fetal sheep - Wu, Wentao; Teng, Yun; Tian, Miao; Huang, Bingxin; Deng, Yuhang; Li, Huili; Yuan, Haiyun; Chen, Jimei; Li, Xiaohong; Zhou, Chengbin (Frontiers in Cardiovascular Medicine, 2022)
Objective Fetal cardiopulmonary bypass (CPB) is essential to fetal heart surgery, while its development is limited by vital organ dysfunction after CPB. Studying organ metabolism may help to solve this problem. The objective of this study was to describe the tissue-specific metabolic fingerprints of fetal sheep under CPB and to associate them with organ functions. Methods Ten pregnant ewes at 90–120 days of gestation were randomly divided into two groups. The bypass group underwent a 1-h fetal CPB, whereas the control group underwent only a fetal sternotomy. During bypass, echocardiography, blood gases, and blood biochemistry were measured. After bypass, lambs were sacrificed, and tissues of the heart, liver, brain, kidney, and placenta were harvested. The metabolites extracted from these tissues were analyzed using non-targeted metabolomics based on liquid chromatography-mass spectrometry techniques. Results All tissues except the placenta displayed significant metabolic changes, and the fetal heart displayed obvious functional changes. Fetal sheep that underwent CPB had common and tissue-specific metabolic signatures. These changes can be attributed to dysregulated lipid metabolism, altered amino acid metabolism, and the accumulation of plasticizer metabolism. Conclusion Fetal CPB causes tissue-specific metabolic changes in fetal sheep. Studying these metabolic changes, especially cardiac metabolism, is of great significance for the study of fetal CPB.